Las técnicas grafo plásticas como estrategia didáctica para desarrollar la creatividad en los niños/as de primer grado básico - Peralta Cumbe, Helen (2014)
The purpose of this research project is the correct application of the visual graph techniques in the development of creativity, the teachers of the School of Basic Education Complete Morning , Evening and Night Prosecutor José Martínez Queirolo, cooperative Juan Montalvo of 8 Km ½ way Daule of the Province of Guayas not correctly apply the techniques, most of these are repeated. Plastic art is important because it is an enabler through integrated learning for the training of students…..